ONOVLENNJA UČNIVSTVA V SUČASNIJ JEVANHELʹSʹKIJ SPILʹNOTI JAK POVERNENNJA DO NOVOZAVITNOHO IDEALU = Renewing Discipleship in Today’s Evangelical Community as a Return to the New Testament Ideal - Stankevych, Vitalii (Bogoslovskie razmyšlenija, 2020)
This article examines the possibility of renewing the evangelical ecclesiological community through the renewal of discipleship as the New Testament ideal. Evangelical theologians generally agree that modern Christian society and society as a whole require some kind of renewal. Increasingly, renewal is understood as a return to biblical ideals. One of these ideals is discipleship. New Testament discipleship should be regarded as a holistic phenomenon, the ideal of which is the example of the disciples’ training as left to us by Jesus Christ. At present, by Christian discipleship is meant various practices related to the idea of a teacher-student relationship. In general,the idea of a return to interpersonal relations in the context of discipleship is what the church can offer society in the postmodern era. The article presents the reasoning of attempts to renew the church community through the renewal of New Testament discipleship. The grounds for updating the modern church community are given. The main features of New Testament discipleship in the context of the relationship between Jesus and the disciples are presented. In addition, examples of the implementation of New Testament discipleship in two Ukrainian evangelical communities are offered.To restore discipleship, transformation within the church is necessary. An analysis of modern discipleship practices found that, on the one hand, the church is not ready for reform, although it is necessary, and, on the other hand, it is in search of an alternative. A return to holistic New Testament discipleship is possible with a systemic reform of the evangelical church. It is necessary to bring about a revival of empathy, which is preceded by the restoration of interpersonal relations as an indicator of true membership in the ekklesia.